Business vocabulary in use : Intermediate and upper-intermediate - Mascull, Bill. (Nxb Trẻ, 2002)
Introduction; Jobs, people and organizations; Production; Marketing; Money; Finance and economy; Doing the right thing; Personal skill; Culture; Telephone, fax and email; Business skill; Answer key, Index.